PELATIHAN PEMBUATAN PANGAN FUNGSIONAL KOMBUCHA DAN MANISAN BUAH PEDADA (Sonneratia caseolaris) DI SMA NEGERI 1 TARAKAN - Luthfiyana, Novi; Bija, Stephanie; Mutmainnah, Mutmainnah; Samsuriadi, Samsuriadi; Aeni, Nur; Raraq, Eva (Universitas Mataram, 2024)
The public awareness of the importance of quality of life is formed by making functional food an alternative to improve health. The availability of abundant Sonneratia sp. or pada mangrove fruit and good metabolite content make pada fruit an alternative functional food, including dried fruit candy and kombucha. This activity aims to increase scientific knowledge and the application of appropriate technology through education and training in diversifying pada fruit as a functional food. This activity was conducted on July 31-August 12, 2024, at SMAN 1 Tarakan. The method of this activity consists of three stages. The first is delivering educational material related to introducing mangrove fruit types and their potential as functional food. The second stage is training and assistance in making pada fruit candy and kombucha. The third stage is evaluation and monitoring at the end of the activity to determine the partner's understanding and success. This training activity shows that partners understand that pada fruit from various mangrove plants in the North Kalimantan region can be directly used as a functional food. The training phase produced dried candied pada and three types of kombucha derived from green tea, butterfly pea flower tea and rosella flower tea. In the evaluation process of the activity, the obstacles identified were the desired carbonation level in kombucha and the shelf life of candied fruit. The training increased partners' insight by 80% into utilizing pada in creative and innovative health products (kombucha and candied fruit).